Oxidation and reduction leaching process
By contacting the lithium-ion battery material with an acidic aqueous solution in the presence of sulfur dioxide, copper sulfide is formed, and purified by solid-liquid and solid-solid separation technology, the problem of low recovery efficiency of lithium and copper is solved, and efficient and economical recycling effect is achieved.
Patent Information
- Application Number
- CN202380058101.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to efficiently recover and purify lithium and other valuable metals, such as copper, from lithium-ion battery materials, and the leaching method efficiency is affected.
In the presence of sulfur dioxide, the lithium-ion battery material is contacted with an acidic aqueous solution with a pH of less than 6 to form copper sulfide, and the composition is purified by solid-liquid and solid-solid separation techniques.
Efficient recovery of lithium and copper from lithium-ion battery materials is achieved, improving recovery and purity, and simplifying the process flow.
Smart Images

Figure CN119654429A_ABST
Abstract
Description
[0001] The project leading to this application has received funding from the Federal Ministry for Economic Affairs and Climate Action (Bundesministerium für Wirtschaft und Klimaschutz) (Germany; FKZ: 16BZF101A); the applicants are responsible for all disclosures in this article.
[0002] Disclosed herein are methods for obtaining compositions comprising copper sulfide from materials, wherein the methods comprise: contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide to form copper sulfide; wherein the material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide, and copper hydroxide, and wherein the material comprises an amount of zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode. Also disclosed are methods for recycling at least one battery material, and compositions comprising copper sulfide.
[0003] Lithium ion battery materials and valuable metal ores are complex mixtures of various elements and compounds. For example, many lithium ion battery materials contain valuable metals, such as lithium, aluminum, nickel, cobalt, copper, and / or manganese. It may be desirable to recover various elements and compounds from lithium ion battery materials and valuable metal ores. For example, it may be advantageous to recover lithium, aluminum, nickel, cobalt, copper, and / or manganese.
[0004] High-purity lithium is a valuable resource. Many lithium sources, such as lithium-ion batteries, lithium-ion battery waste, lithium-containing water (e.g., groundwater), and raw lithium-containing ores, are complex mixtures of various elements and compounds. Removing and purifying lithium from materials such as lithium-ion battery materials is an exemplary step in lithium-ion battery recycling. Lithium-ion battery materials are complex mixtures of various elements and compounds, and it may be desirable to remove various non-lithium impurities. Such impurities may exist in various oxidation states, which may affect, for example, the efficiency of a leaching method. For example, in some leaching methods, high oxidation state metals may be more efficiently or less efficiently leached than low or zero oxidation state metals. Some non-lithium impurities are also valuable resources, and it may be additionally desirable to separate and purify various elements and compounds from such materials.
[0005] Accordingly, methods for removing lithium from materials such as battery materials and methods for recycling lithium-ion battery materials are needed. In addition, for example, methods for extracting valuable metals such as copper are needed. For example, leaching methods for efficiently and effectively leaching complex mixtures of various elements and compounds such as mixed metals coexisting in various oxidation states are needed. For example, economic methods with high lithium recovery and high lithium purity are needed. Economic methods with high recovery and high purity for removing valuable metals such as nickel, copper and cobalt from materials are also needed.
[0006] CN 114 634 192A discloses a method and device for recycling black matter from waste lithium-ion batteries. The method uses black matter obtained from lithium iron phosphate batteries. The method for recycling black matter from waste lithium-ion batteries comprises the following steps: adding a solvent to the black matter, stirring to prepare a slurry, then adding oxygen, sulfur dioxide and a first inorganic acid solution to the slurry for reaction, and filtering the slurry after the reaction to obtain a first recycling material and a first solution; wherein the first recycling material contains iron phosphate, and the first solution contains Li + By adding oxygen, sulfur dioxide and a small amount of inorganic acid to the slurry containing black matter, oxygen and sulfur dioxide will convert Fe in lithium iron phosphate into 2+ Oxidation to form Fe 3+ , and Fe 3+ With PO4 in lithium iron phosphate 3- The reaction forms precipitated iron phosphate. A soluble carbonate is added to the first solution to precipitate lithium carbonate, and lithium carbonate and a second solution are obtained by filtration.
[0007] Methods for obtaining compositions comprising copper sulfide from materials are disclosed, wherein the methods comprise: contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide to form copper sulfide; wherein no oxidant is added during the contacting step; wherein the material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide, and copper hydroxide, and wherein the material comprises an amount of zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
[0008] In some embodiments, the method further comprises separating the composition comprising copper sulfide from the aqueous solution by solid-liquid separation.
[0009] In some embodiments, the method further comprises purifying the composition comprising copper sulfide by solid-solid separation.
[0010] In some embodiments, the composition comprises 0.1 weight percent to 100 weight percent, such as 1 weight percent to 100 weight percent, of copper sulfide, based on the total weight of the composition.
[0011] In some embodiments, the acidic aqueous solution comprises H2SO4.
[0012] In some embodiments, the material is a lithium ion battery material comprising one or more selected from the group consisting of: a black substance, a cathode active material, a cathode, a cathode current collector foil, a cathode active material precursor, graphite, an anode, an anode current collector foil, and combinations thereof.
[0013] In some embodiments, the material comprises: 0 to 10 weight percent lithium, 0.1 to 60 weight percent nickel, 0 to 20 weight percent cobalt, 0.1 to 20 weight percent aluminum, 0 to 20 weight percent iron, 0 to 20 weight percent manganese, and 0 to 20 weight percent zinc; wherein each weight percent is based on the total weight of the material; wherein an amount of at least one of the nickel, cobalt, aluminum, iron, manganese, and zinc is present as a zero oxidation state metal; and wherein the material has a molar ratio of copper in the range of 1:0.1 to 1:10 to an amount of zero oxidation state metals having a standard redox potential less than 0 volts relative to a standard hydrogen electrode.
[0014] In some embodiments, the material or a precursor thereof is pyrolyzed prior to the contacting step.
[0015] In some embodiments, contacting the material with an acidic aqueous solution having a pH less than 6 in the presence of sulfur dioxide causes the formation of hydrogen and hydrogen sulfide gases, and wherein after the hydrogen and hydrogen sulfide gases are formed, the method includes adding an oxidant selected from O2, N2O, a mixture of air and 0.1 to 5 vol% sulfur dioxide, a mixture of oxygen and 0.1 to 5 vol% sulfur dioxide, and combinations thereof.
[0016] In some embodiments, the method further comprises adding air after the contacting step.
[0017] In some embodiments, the acidic aqueous solution has an acid concentration ranging from 18 mol / L to 0.0001 mol / L.
[0018] In some embodiments, during the contacting step, sulfur dioxide is fed as a gas at a rate of 1 to 500 Nl / kg of material.
[0019] In some embodiments, after the contacting step, the method further comprises adding an additional material comprising one or more selected from the group consisting of metal oxides, metal hydroxides, metal carbonates, metal bicarbonates, and combinations thereof.
[0020] Also disclosed are methods for recycling at least one battery material selected from lithium-ion batteries, lithium-ion battery waste, lithium-ion battery production waste, lithium-ion battery cell production waste, lithium-ion cathode active materials, and combinations thereof, wherein the methods include: optionally, heat treating the at least one battery material at a temperature ranging from 350°C to 900°C, mechanically crushing the at least one battery material to obtain a crushed material, optionally, sorting the crushed material to obtain a fine fraction (e.g., black matter) and a coarse fraction, and subjecting the crushed material, optionally the black matter, the coarse fraction, or the fine fraction and the coarse fraction to the leaching method disclosed herein.
[0021] In some embodiments, the method further comprises smelting the composition comprising copper sulfide.
[0022] In some embodiments, the method further comprises calcining the composition comprising copper sulfide.
[0023] Also disclosed are compositions comprising copper sulfide prepared according to the methods disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 An exemplary batch process consistent with some embodiments of the present disclosure is depicted.
[0025] Figure 2 An exemplary continuous process consistent with some embodiments of the present disclosure is depicted.
[0026] Figure 3 An XRD pattern of an exemplary black substance is depicted.
[0027] definition:
[0028] As used herein, "a" or "an" entity refers to one or more of that entity, e.g., "a compound" refers to one or more compounds or at least one compound, unless otherwise specified. Thus, the terms "a" (or "an"), "one or more", and "at least one" are used interchangeably herein.
[0029] As used herein, the term "material" refers to an element, component, and / or substance that makes up or can be made into something.
[0030] As used herein, a "reducing agent" is a compound that can reduce a metal oxide and / or a metal hydroxide. For example, some reducing agents can reduce some metal oxides and / or some metal hydroxides, but cannot reduce other metal oxides and / or metal hydroxides.
[0031] As used herein, an "oxidant" is a compound that is capable of oxidizing a metal in an oxidation state of zero. For example, some oxidants are capable of oxidizing some metals in an oxidation state of zero, but not other metals in an oxidation state of zero.
[0032] As used herein, a "solution" is a combination of a fluid and one or more compounds. For example, each of the one or more compounds in the solution may or may not be dissolved in the fluid.
[0033] As used herein, a "substantially pure metal ion solution" is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 50% by weight excluding the weight of the solvent.
[0034] As used herein, a "substantially pure solid metal ion salt" is a solid comprising a metal ion and a counterion; wherein the combined weight of the metal ion and the counterion is at least 50% by weight of the solid excluding the weight of the solvent.
[0035] As used herein, the term "bubbling" refers to the dispersion of a gas through a liquid.
[0036] As used herein, the term "base" refers to a material that is capable of reacting with hydronium ions and increasing the pH of an acidic solution.
[0037] As used herein, the term "standard electrode potential" has its common usage in the field of electrochemistry and is the value of the electromotive force of an electrochemical cell in which molecular hydrogen is oxidized to solvated protons at a standard hydrogen electrode at 1 bar and 298.15 K. By definition, the potential of the standard hydrogen electrode is 0 volts. An exemplary reference is: Johnstone, AH, CRC Handbook of Chemistry and Physics - 69th Edition, ed. RC Weast, CRC Press Inc., Boca Raton, Florida, 1988.
[0038] As used herein, the term "smelting" refers to heating a material above its melting temperature, optionally in the absence of oxygen.
[0039] As used herein, the term "calcining" refers to heating a material to below its melting temperature, optionally in the presence of oxygen.
[0040] As used herein, the term "mixed hydroxide precipitate" refers to a material comprising at least two metal hydroxides. An exemplary mixed hydroxide precipitate is a commercially available MHP produced by MCC (Metallurgical Corporation of China) at the Ramu plant in PNG (Papua New Guinea), which is produced according to the following procedure: (1) HPAL (high pressure acid leaching) sulfuric acid leaching of the limonite laterite ore fraction, (2) neutralization of residual acid using CaCO3 to raise the pH and remove Fe / Al by precipitation, (3) precipitation of Ni and Co from the separated PLS as MHP using NaOH, and (4) a final precipitation step using CaO - this second stage precipitate is recycled back to the autoclave discharge slurry for neutralization, where Ni and Co (and Mn) are re-leached.
[0041] Methods for obtaining compositions comprising copper sulfide from materials are disclosed, wherein the methods comprise: contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide to form copper sulfide; wherein the material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide, and copper hydroxide, and wherein the material comprises an amount of zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
[0042] Material:
[0043] The material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide, and copper hydroxide, and the material comprises an amount of zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
[0044] In some embodiments, the material is a lithium-ion battery material, which includes one or more selected from the following: a black substance, a cathode active material, a cathode, a cathode current collector foil (e.g., containing aluminum), a cathode active material precursor, graphite, an anode, an anode current collector foil (e.g., containing copper), and combinations thereof.
[0045] In some embodiments, the material comprises: 0 to 10 weight percent lithium, 0.1 to 60 weight percent nickel, 0 to 20 weight percent cobalt, 0.1 to 20 weight percent aluminum, 0 to 20 weight percent iron, 0 to 20 weight percent manganese, and 0 to 20 weight percent zinc; wherein each weight percent is based on the total weight of the material; wherein an amount of at least one of the nickel, cobalt, aluminum, iron, manganese, and zinc is present as a zero oxidation state metal; and wherein the material has a molar ratio of copper in the range of 1:0.1 to 1:10 (e.g., 1:1 to 1:5, including, for example, 1:1.5 or 1:3) to an amount of zero oxidation state metals having a standard redox potential less than 0 volts relative to a standard hydrogen electrode.
[0046] In some embodiments, the material comprises one or more metals in a zero oxidation state and one or more selected from metal oxides, metal hydroxides, metal carbonates, and combinations thereof.
[0047] In some embodiments, the material is a lithium ion battery material including one or more selected from the group consisting of a black substance, a cathode active material, a cathode, a cathode active material precursor, and combinations thereof.
[0048] In some embodiments, the material comprises one or more selected from nickel, cobalt, manganese, and combinations thereof.
[0049] In some embodiments, the one or more metals in the zero oxidation state are selected from nickel, cobalt, copper, aluminum, iron, manganese, rare earth metals, and combinations thereof.
[0050] In some embodiments, the metal oxide is selected from nickel oxide, cobalt oxide, copper oxide, aluminum oxide, iron oxide, manganese oxide, rare earth oxide, and combinations thereof.
[0051] In some embodiments, the metal hydroxide is selected from nickel hydroxide, cobalt hydroxide, copper hydroxide, aluminum hydroxide, iron hydroxide, manganese hydroxide, rare earth hydroxides, and combinations thereof.
[0052] In some embodiments, the material includes: 0.1 weight percent to 10 weight percent lithium, 0 weight percent to 60 weight percent nickel, 0 weight percent to 20 weight percent cobalt, 0 weight percent to 20 weight percent copper, 0 weight percent to 20 weight percent aluminum, 0 weight percent to 20 weight percent iron, and 0 weight percent to 20 weight percent manganese; wherein each weight percent is based on the total weight of the material.
[0053] In some embodiments, the material or its precursor is pyrolyzed prior to leaching. In some embodiments, the pyrolysis is performed under an inert atmosphere, an oxidizing atmosphere, a reducing atmosphere, or a combination thereof.
[0054] In some embodiments, the material is a lithium ion battery material including one or more selected from the group consisting of a black substance, a cathode active material, a cathode, a cathode active material precursor, and combinations thereof.
[0055] "Black matter" refers to a material containing lithium, which is obtained by mechanical methods such as mechanical pulverization from, for example, lithium-ion batteries, lithium-ion battery waste, lithium-ion battery production waste, lithium-ion battery cell production waste, lithium-ion cathode active materials, and / or combinations thereof. For example, black matter can be obtained from battery waste by mechanically treating the battery waste to obtain active components of electrodes such as graphite and cathode active materials, and may contain impurities from casings, electrode foils, cables, diaphragms, and electrolytes. In some instances, the battery waste can be subjected to heat treatment to pyrolyze organic (e.g., electrolytes) and polymer (e.g., diaphragms and adhesives) materials. Such heat treatment can be performed before or after the mechanical pulverization of the battery material. In some embodiments, the black matter is subjected to heat treatment.
[0056] Lithium-ion batteries can be disassembled, punched, ground (e.g. in a hammer mill, rotary mill), and / or, for example, shredded (in an industrial shredder). The active materials of the battery electrodes can be obtained by such mechanical processing. Light fractions (e.g. housing parts made of organic plastics and aluminum or copper foil) can be removed, for example, by forced air flow, air separation or classification or screening.
[0057] Battery waste can be derived from, for example, waste batteries or production waste such as rejected materials. In some embodiments, the material is obtained from mechanically processed battery waste, such as battery waste processed in a hammer mill, rotary mill, or industrial shredder. Such material can have an average particle size (D50) ranging from 1 μm to 1 cm, such as 1 μm to 500 μm, and further such as 3 μm to 250 μm.
[0058] Larger parts of the battery waste, like housings, wiring and electrode carrier films, can be separated mechanically, so that the corresponding materials can be excluded from the battery material used in the method.
[0059] The mechanically treated battery waste can be subjected to a solvent treatment in order to dissolve and separate the polymer binder used to bind the transition metal oxide to the current collector film, or, for example, to bind graphite to the current collector film. Suitable solvents are N-methylpyrrolidone, N,N-dimethyl-formamide, N,N-dimethylacetamide, N-ethylpyrrolidone and dimethyl sulfoxide, in pure form, as a mixture of at least two of the foregoing, or as a mixture with 1% to 99% by weight of water.
[0060] In some embodiments, the mechanically treated battery waste can be subjected to heat treatment in different atmospheres over a wide temperature range. In some embodiments, the temperature range is 100°C to 900°C. In some embodiments, lower temperatures below 300°C can be used to evaporate residual solvents in the battery electrolyte, at higher temperatures, the binder polymer may decompose, and at temperatures above 400°C, the composition of the inorganic material may change because some transition metal oxides may be reduced by carbon contained in the waste or by the introduction of reducing gases. In some embodiments, reduction of lithium metal oxides can be avoided by maintaining the temperature below 400°C and / or by removing carbonaceous materials prior to heat treatment.
[0061] In some embodiments, the heat treatment is carried out at a temperature ranging from 350°C to 900°C. In some embodiments, the heat treatment is carried out at a temperature ranging from 450°C to 800°C. In some embodiments, the heat treatment is carried out under an inert, oxidizing or reducing atmosphere. In some embodiments, the heat treatment is carried out under an inert or reducing atmosphere. In some embodiments, the reducing agent is formed by pyrolyzed organic (polymer) components under heat treatment conditions. In some embodiments, the reducing agent is formed by adding a reducing gas such as H2 and / or CO.
[0062] In some embodiments, the material includes at least one selected from the group consisting of lithiated nickel cobalt manganese oxide, lithiated nickel cobalt aluminum oxide, lithium metal phosphate, lithium ion battery waste, black matter, and combinations thereof.
[0063] In some embodiments, the material includes a material having the formula Li x The lithium metal phosphate of MPO4, wherein x is an integer greater than or equal to 1, and M is selected from the group consisting of metals, transition metals, rare earth metals, and combinations thereof.
[0064] In some embodiments, the material includes a material having the formula Li 1+x (Ni a Co b Mn c M 1 d ) 1-x O2 lithiated nickel cobalt manganese oxide, where M 1Selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V, and Fe, 0 ≤ x ≤ 0.2, 0.1 ≤ a ≤ 0.95, 0 ≤ b ≤ 0.9 (such as 0.05 < b ≤ 0.5), 0 ≤ c ≤ 0.6, 0 ≤ d ≤ 0.1, and a + b + c + d = 1. Exemplary lithium nickel cobalt manganese oxides include Li (1+x) [Ni 0.33 Co 0.33 Mn 0.33 (1-x) O2, Li (1+x) [Ni 0.5 Co 0.2 Mn 0.3 (1-x) O2, Li (1+x) [Ni 0.6 Co 0.2 Mn 0.2 (1-x) O2, Li (1+x) [Ni 0.7 Co 0.2 Mn 0.3 (1-x) O2, Li (1+x) [Ni 0.8 Co 0.1 Mn 0.1 (1-x) O2 (each having x as defined above), and Li[Ni 0.85 Co 0.13 Al 0.02 O2.
[0065] In some embodiments, the material comprises a lithium nickel cobalt aluminum oxide having the formula Li[Ni h Co i Al j O 2+r where h ranges from 0.8 to 0.95, i ranges from 0.1 to 0.3, j ranges from 0.01 to 0.10, and r ranges from 0 to 0.4.
[0066] In some embodiments, the material comprises a lithium manganese oxide having the formula Li (1+x) Mn 2-x-y-z M y M’ z O4, where x ranges from 0 to 0.2; y + z ranges from 0 to 0.1; and M ’ is selected from Al, Mg, Fe, Ti, V, Zr, and Zn.
[0067] In some embodiments, the material comprises a material having the formula xLi (1+1 / 3) M (2 / 3) A compound of O2·yLiMO2·zLiM’O2, where M contains at least one metal among Mn, Ni, Co with an oxidation state of +4, M’ is at least one transition metal, and 0 < x < 1, 0 < y < 1, 0 < z < 1 and x + y + z = 1.
[0068] In some embodiments, the material contains nickel, cobalt, manganese, copper, aluminum, iron, phosphorus, or a combination thereof.
[0069] In some embodiments, the material has a weight ratio of lithium to the total weight of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 10. In some embodiments, the material has a weight ratio of lithium to the total weight of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 5. In some embodiments, the material has a weight ratio of lithium to the total weight of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 2. In some embodiments, the material has a weight ratio of lithium to the total weight of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 1.
[0070] In some embodiments, the material includes Li x MO2, where x is an integer greater than or equal to 1, and M is selected from metals, transition metals, rare earth metals, and combinations thereof.
[0071] In some embodiments, a method for recycling lithium-ion battery materials includes mechanically pulverizing at least one selected from lithium-ion batteries, lithium-ion battery waste, lithium-ion battery production waste, lithium-ion battery cell production waste, lithium-ion cathode active materials, and combinations thereof to obtain a black substance.
[0072] In some embodiments, the material has a standard electrode potential in the range of +1.1V to -1.7V. In some embodiments, based on the total weight of the material, 0.1 wt% to 10 wt% of the material has a standard electrode potential in the range of +0.1V to +0.8V and 0.1 wt% to 60 wt% of the material has a standard electrode potential in the range of -1.7V to -0.01V.
[0073] In some embodiments, one or more metals in the zero oxidation state each have a standard electrode potential in the range of 1.1V to -1.7V. In some embodiments, one or more metals in the zero oxidation state each have a standard electrode potential in the range of -1.7V to +0.35V. Standard electrode potentials of some exemplary metals in the zero oxidation state include: Al / Al 3+ (E(0) = -1.66V), Cu / Cu 2+ (E(0) = +0.35V), Co / Co 2+ (E(0) = -0.28V), Fe / Fe 2+(E(0) = -0.44 V), and Ni / Ni 2+ (E(0) = -0.23 V).
[0074] In some embodiments, one or more selected from metal oxides, metal hydroxides, and combinations thereof each have a standard electrode potential ranging from +0.1 V to +1.9 V. In some embodiments, one or more selected from metal oxides, metal hydroxides, and combinations thereof each have a standard electrode potential ranging from 0.15 V to 1.83 V. Some exemplary metal ions, such as metal ions that may be produced by dissolution of an oxide or hydroxide, and standard electrode potentials of metal oxides and / or metal hydroxides include: Co 3+ / Co 2+ (E(0)=+1.83V),NiO2+4H + / Ni 2+ +2H2O(E(0)=+1.678V),Mn 3+ / Mn 2+ (E(0) = +1.5415 V), and Mn(OH)3 / Mn(OH)2+OH-(E(0) = +0.15 V).
[0075] method:
[0076] Methods for obtaining compositions comprising copper sulfide from materials are disclosed, wherein the methods comprise: contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide to form copper sulfide; wherein no oxidant is added during the contacting step; wherein the material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide, and copper hydroxide, and wherein the material comprises an amount of zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
[0077] In some embodiments, the method further comprises separating the composition comprising copper sulfide from the aqueous solution by solid-liquid separation (eg, filtration, sedimentation, and / or centrifugation).
[0078] In some embodiments, the method further comprises purifying the composition comprising copper sulfide by solid-solid separation (e.g., flotation, magnetic separation using magnetic carrier particles capable of forming magnetic agglomerates with copper sulfide particles, gravity separation, and / or dense media separation).
[0079] No oxidant is added during the contacting step. In particular, no air, O2, or NO2 is added during the contacting step. The material is contacted with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide, the reaction of the acid with the zero oxidation state metal present in the material having a standard redox potential of less than 0 volts relative to the standard hydrogen electrode, resulting in the formation of hydrogen. The reaction of the hydrogen formed with the sulfur dioxide in turn results in the formation of hydrogen sulfide, which then reacts with the copper present in the material to form copper sulfide. Therefore, the presence of an oxidant capable of oxidizing hydrogen or preventing the reduction of sulfur dioxide to sulfide would be disadvantageous, and the addition of an oxidant during the contacting step should be avoided until after the hydrogen has been formed, i.e., after the copper sulfide has been formed.
[0080] In some embodiments of the method, the acidic aqueous solution is not bubbled with an oxidizing agent (eg, air) prior to the contacting step.
[0081] Contacting the material with an acidic aqueous solution having a pH of less than 6 includes first contacting the material with an acid in the presence of sulfur dioxide, resulting in the formation of hydrogen gas and the formation of hydrogen sulfide gas.
[0082] In some embodiments, contacting the material with an acidic aqueous solution having a pH less than 6 causes formation of hydrogen gas, and the acidic aqueous solution having a pH less than 6 is contacted with sulfur dioxide during the formation of hydrogen gas.
[0083] In some embodiments, SO2 is purged through the solution at a rate of up to 20% solution volume / minute for 1 to 3 hours. SO2 is not provided as a mixture with O2 or air. In some embodiments, SO2 is provided as a pure gas having a purity of at least 90%, such as 99%, or as a mixture with an inert gas such as, for example, nitrogen and / or argon.
[0084] In some embodiments, excess sulfur dioxide is recycled from the exhaust gas back to the reactor.
[0085] In some embodiments, the contacting step is performed at ambient temperature. In some embodiments, the contacting step is performed at a temperature ranging from 50° C. to 110° C. In some embodiments, the contacting step is performed for a duration ranging from 2 hours to 4 hours.
[0086] In some embodiments, the acidic aqueous solution has a pH in the range of -1.0 to 3.
[0087] In some embodiments, the method includes an oxidation step during which an oxidant is added to the acidic aqueous solution and the oxidation step is after the contacting step. In some embodiments, the acidic aqueous solution is not bubbled with air prior to the contacting step. In some embodiments, an oxidant other than sulfuric acid is not added to the acidic aqueous solution prior to the contacting step.
[0088] In some embodiments, a mixture of SO2 and O2 or air (containing 5% or more SO2) is used as the oxidant. In some embodiments, excess oxidizing gas O2 (such as in air) and / or N2O is recycled from the exhaust gas back to the leaching reactor.
[0089] In some embodiments of the method, the oxidant is not added until after the hydrogen is formed. In some embodiments, the oxidant is not added until at least 1 minute, at least 10 minutes, at least 30 minutes, at least 1 hour, or at least 2 hours after the contacting step begins.
[0090] In some embodiments, the black matter is slurried in water at a weight percentage of the black matter ranging from 5% to 30% based on the total weight of the slurry. In some embodiments, the slurried black matter is contacted with an acidic aqueous solution having a pH of less than 6. In some embodiments, the acidic aqueous solution having a pH of less than 6 is formed from the slurried black matter by adding an acid and / or an oxidizing agent. In some embodiments, the weight ratio of H2SO4 to the black matter in the acidic aqueous solution ranges from 1:1 to 2:1. In some embodiments, H2SO4 is added during the contacting step to adjust the pH.
[0091] In some embodiments, the black material is provided as a slurry. In some embodiments, the black material is provided as a slurry in water. In some embodiments, the black material is provided as a slurry in an aqueous side stream from a subsequent processing step, such as, for example, a wash liquid from a filter. In some embodiments, the black material is provided as a solid. In some embodiments, the cathode active material is provided as a slurry. In some embodiments, the cathode active material is provided as a slurry in water. In some embodiments, the cathode active material is provided as a slurry in an aqueous side stream from a subsequent processing step, such as, for example, a wash liquid from a filter. In some embodiments, the cathode active material is provided as a solid. In some embodiments, the mixed hydroxide precipitate is provided as a slurry. In some embodiments, the mixed hydroxide precipitate is provided as a slurry in water. In some embodiments, the mixed hydroxide precipitate is provided as a slurry in water. In some embodiments, the mixed hydroxide precipitate is provided as a slurry in an aqueous side stream from a subsequent processing step, such as, for example, a wash liquid from a filter. In some embodiments, the mixed hydroxide precipitate is provided as a solid.
[0092] In some embodiments, a zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode is added to the material before or during contacting the material with the acid. Such metals may include, for example, nickel, cobalt, manganese, iron, zinc, and / or aluminum.
[0093] In some embodiments, nickel is added if the material comprises battery material derived from a nickel-containing battery.
[0094] In some embodiments, if the material comprises battery material derived from a battery containing cobalt, cobalt is added.
[0095] In some embodiments, manganese is added if the material comprises battery material derived from a manganese containing battery.
[0096] In some embodiments, iron is added if the material comprises battery material derived from an iron containing (eg, lithium iron phosphate) battery.
[0097] In some embodiments, after the contacting step, the method further comprises adding a base. In some embodiments, the base is selected from CaO, hydroxide salts, carbonates, and combinations thereof. In some embodiments, the hydroxide salt is selected from LiOH, NaOH, KOH, NH4OH, Ca(OH)2, CaCO3, Ni(OH)2, Co(OH)2, Mn(OH)2, and combinations thereof. In some embodiments, the hydroxide salt is a mixed hydroxide precipitate obtained from nickel laterite ore processing.
[0098] In some embodiments, the method is performed batchwise.
[0099] In some embodiments, the method is performed continuously in at least two reaction vessels. In some embodiments, the method is performed continuously in, for example, three, four, five, six, seven or more reaction vessels. In some embodiments, the black substance is added to the first reaction vessel, the oxidant is added to the second and / or third reaction vessel, the cathode active material and / or the mixed hydroxide precipitate is added to the fourth reaction vessel, and the reductant is added to the fourth, fifth and / or sixth reaction vessel.
[0100] In some embodiments, a reflux condenser is fitted to at least one reaction vessel.
[0101] In some embodiments, contacting the material with the acidic aqueous solution is performed at ambient pressure. In some embodiments, contacting the material with the acidic aqueous solution is performed at elevated pressure.
[0102] In some embodiments, the contacting step is for a duration ranging from 10 minutes to 10 hours at a temperature ranging from 20°C to 100°C. In some embodiments, the contacting step is for a duration ranging from 3 hours to 5 hours at 100°C. In some embodiments, the contacting step is for a duration ranging from 3 hours to 5 hours at 60°C. In some embodiments, the contacting step is for a duration ranging from 3 hours to 5 hours at 25°C.
[0103] In some embodiments, the disclosed methods include leaching a material according to the methods disclosed herein to obtain an aqueous solution comprising metal ions, and separating the metal ions to obtain at least one substantially pure metal ion solution and / or at least one substantially pure solid metal ion salt.
[0104] In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 50% by weight of the solid excluding the weight of the solvent, such as all water. In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 70% by weight of the solid excluding the weight of the solvent. In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 80% by weight of the solid excluding the weight of the solvent. In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 90% by weight of the solid excluding the weight of the solvent. In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 95% by weight of the solid excluding the weight of the solvent. In some embodiments, a substantially pure solid metal ion salt is a solid comprising a metal ion and a counterion; wherein the total weight of the metal ion and the counterion is at least 99% by weight of the solid excluding the weight of the solvent.
[0105] In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 50% by weight of the solution excluding the weight of the solvent. In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 70% by weight of the solution excluding the weight of the solvent. In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 80% by weight of the solution excluding the weight of the solvent. In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 90% by weight of the solution excluding the weight of the solvent. In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counterions, and a solvent; wherein the total weight of the metal ions and counterions is at least 95% by weight of the solution excluding the weight of the solvent. In some embodiments, a substantially pure metal ion solution is a solution comprising metal ions, counter ions, solvent; wherein the total weight of the metal ions and counter ions is at least 99% by weight of the solution excluding the weight of the solvent.
[0106] In some embodiments, separating the metal ions to obtain at least one substantially pure metal ion solution and / or at least one substantially pure solid metal ion salt comprises one or more of solid / liquid separation, extraction, precipitation, crystallization, and combinations thereof.
[0107] In some embodiments, the method may be performed partially or entirely as a continuous method controlled by sensors and actuators as part of a computer-based process control system.
[0108] In some embodiments, the method further comprises smelting the composition comprising copper sulfide.
[0109] In some embodiments, the method further comprises calcining the composition comprising copper sulfide.
[0110] Compositions comprising copper sulfide:
[0111] Disclosed herein are compositions comprising copper sulfide.
[0112] In some embodiments, compositions comprising copper sulfide are prepared according to the methods disclosed herein.
[0113] In some embodiments, the composition comprising copper sulfide comprises copper (II) sulfide (CuS) and / or copper (I) sulfide (Cu2S). In some embodiments, the composition comprising copper sulfide further comprises copper metal and sulfur.
[0114] In some embodiments, the copper sulfide species is amorphous.
[0115] In some embodiments, the composition comprising copper sulfide comprises 2.5 to 100 weight % copper sulfide by the total weight of the composition. In some embodiments, the composition comprising copper sulfide comprises 10 to 100 weight % copper sulfide by the total weight of the composition. In some embodiments, the composition comprising copper sulfide comprises 25 to 100 weight % copper sulfide by the total weight of the composition. In some embodiments, the composition comprising copper sulfide comprises 2.5 to 30 weight % copper sulfide by the total weight of the composition. In some embodiments, the composition comprising copper sulfide comprises 10 to 30 weight % copper sulfide by the total weight of the composition. In some embodiments, the composition comprising copper sulfide comprises 25 to 50 weight % copper sulfide by the total weight of the composition.
[0116] In some embodiments, the composition comprising copper sulfide is separated from the aqueous solution by solid-liquid separation. In some embodiments, the composition comprising copper sulfide is separated from the aqueous solution by at least one solid-liquid separation selected from filtration, sedimentation, and centrifugation.
[0117] In some embodiments, one or more valuable metals are separated by solvent extraction. In some embodiments, one or more of Ni, Co, Mn, Cu, and Li are extracted from the separated liquid by solvent extraction.
[0118] In some embodiments, the composition comprising copper sulfide is purified by solid-solid separation. In some embodiments, the composition comprising copper sulfide is purified by at least one solid-solid separation selected from flotation, magnetic separation, gravity separation, and gravity media separation.
[0119] In some embodiments, copper sulfide is separated from the leach residue by flotation in the presence of xanthate, dithiophosphate, thiocarbamate, xanthogen formate, ester of xanthogenic acid, and / or mercaptobenzothiazole collectors.
[0120] In some embodiments, the carbon contained in the leaching residue is separated by flotation in the presence of a hydrophobic oil (eg, an alkane having more than seven carbon atoms) as a collector.
[0121] In some embodiments, the carbon material is first floated using a hydrophobic oil as a collector and the copper sulfide is secondly floated by using xanthates, dithiophosphates, thiocarbamates, xanthate formates, esters of xanthate and / or mercaptobenzothiazole collectors.
[0122] In some embodiments, copper sulfide is first floated using xanthates, dithiophosphates, thiocarbamates, xanthate formates, esters of xanthate, and / or mercaptobenzothiazole collectors, and carbon material is secondly floated using a hydrophobic oil as a collector.
[0123] An exemplary magnetic separation method is provided in PCT International Application No. PCT / EP2008 / 061503 filed on September 1, 2008. The disclosure of PCT International Application No. PCT / EP2008 / 061503 filed on September 1, 2008 is incorporated herein by reference in its entirety.
[0124] Exemplary methods for separating and purifying compositions comprising copper sulfide are provided in Appl, M. "Ullmann s Encyclopedia of Industrial Chemistry 2011." DOI 10.1002(2012):14356007; which is incorporated herein by reference in its entirety.
[0125] Oxidants:
[0126] In some embodiments, the oxidant comprises O 2. In some embodiments, the oxidant is air.
[0127] In some embodiments, the oxidant has a standard electrode potential ranging from +0.1 V to +1.8 V. In some embodiments, the oxidant has a standard electrode potential ranging from +0.4 V to +1.3 V. In some embodiments, the oxidant has a standard electrode potential ranging from +1 V to +1.5 V.
[0128] reducing agent:
[0129] In some embodiments, the reducing agent has a standard electrode potential in the range of +1 V to -0.5 V. In some embodiments, the reducing agent has a standard electrode potential in the range of +0.2 V to -0.3 V.
[0130] Hydrogen peroxide can act as a reducing agent or an oxidizing agent, depending on the reaction partners. Possible oxidation and reduction reactions are: H2O2 → O2 + 2e - +2H + , and H2O2+2e - +2H + →2H2O. In some embodiments, the standard electrode potential of the reaction partners affects which reaction occurs. For example, under certain conditions, permanganate (MnO4 - ) is reduced by hydrogen peroxide, while Fe 2+ In some embodiments, more acidic conditions favor oxidation reactions because H +to form water, and less acidic conditions favor the reduction reaction because H + In some embodiments, depending on the metal(s) M and the conditions used, the following reactions may or may not occur: 2LiMO2+H2O2+3H2SO4→2LiSO4+2MSO4+4H2O+O2, and M+H2O2+H2SO4→MSO4+2H2O.
[0131] Exemplary Batch Method:
[0132] Figure 1 An exemplary batch method (100) consistent with some embodiments of the present disclosure is depicted. In some embodiments, a material (102), such as a black material comprising nickel, cobalt, copper, and manganese materials, is acid leached in a continuously stirred reaction vessel (101) comprising an acidic aqueous solution having a pH less than 0. In some embodiments, hydrogen gas is evolved (105), and SO2 is added (103) during the evolution of hydrogen gas. In some embodiments, the pH is adjusted to a pH in the range of 1 to 2 with, for example, a cathode active material and / or a mixed hydroxide precipitate, and an oxidant such as O2 and / or N2O is added (104). In some embodiments, the obtained liquid phase (106) and solid phase (105) are separated by solid / liquid separation, such as filtration, centrifugation, and / or sedimentation.
[0133] Exemplary Continuous Process:
[0134] Figure 2 An exemplary continuous method (200) consistent with some embodiments of the present disclosure is depicted. In some embodiments, a material (202), such as a black material comprising nickel, cobalt, copper, and manganese materials, is acid leached in a continuously stirred reaction vessel (201) comprising an acidic aqueous solution having a pH less than 0. In some embodiments, the acid leaching is further performed in one or more additional continuously stirred reaction vessels (203). In some embodiments, SO2 is added (205) to the continuously stirred reaction vessel (204). In some embodiments, the acid leaching in the presence of an added oxidant is further performed in one or more additional continuously stirred reaction vessels (206). In some embodiments, the pH is adjusted to a pH in the range of 1 to 2 with, for example, a cathode active material and / or a mixed hydroxide precipitate, and in some embodiments, an oxidant, such as, for example, O2 and / or N2O, is introduced (208) into the continuously stirred reaction vessel (207). In some embodiments, the leaching in the presence of an added oxidant is further performed in one or more additional continuously stirred reaction vessels (209). In some embodiments, the obtained liquid phase (211) and solid phase (210) are separated by solid / liquid separation such as filtration, centrifugation and / or sedimentation.
[0135] In some embodiments of the method, at the beginning of the contacting step, less than 50 mol% of an oxidant other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of copper in the zero oxidation state and the zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode. In some embodiments, at the beginning of the contacting step, less than 25 mol% of an oxidant other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of copper in the zero oxidation state and the zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode. In some embodiments, at the beginning of the contacting step, less than 10 mol% of an oxidant other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of copper in the zero oxidation state and the zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode. In some embodiments, less than 1 mol% of an oxidant other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of copper in the zero oxidation state and the zero oxidation state metal having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
[0136] In some embodiments of the method, no oxidizing agent is added during the contacting step.
[0137] In some embodiments of the method, the subsequent oxidation step involving the addition of air is initiated at least 1 minute after the contacting step is initiated, at least 10 minutes after the contacting step is initiated, at least 30 minutes after the contacting step is initiated, or at least 1 hour after the contacting step is initiated. In some embodiments, the subsequent oxidation step is initiated between 0 minutes and 2 hours after the contacting step is initiated.
[0138] In some embodiments of the method, the composition comprising copper sulfide is separated by flotation in the presence of a xanthate, a dithiophosphate, a thiocarbamate, a xanthate formates, an ester of xanthate, and / or a mercaptobenzothiazole collector.
[0139] In some embodiments, the method comprises leaching a material to obtain an aqueous solution comprising metal ions, and separating the metal ions to obtain at least one substantially pure metal ion solution and / or at least one substantially pure solid metal ion salt.
[0140] In some embodiments of the method, contacting the material with an acidic aqueous solution having a pH less than 6 causes formation of hydrogen gas, and contacting the acidic aqueous solution having a pH less than 6 with sulfur dioxide during the formation of hydrogen gas.
[0141] If one, more than one, or all of the group members are present in, used in, or otherwise relevant to a given product or method, a claim or description including "or" or "and / or" between at least one member of the group is considered satisfied unless otherwise stated or otherwise obvious from the context. The present disclosure includes embodiments in which exactly one member of the group is present in, used in, or otherwise relevant to a given product or method. The present disclosure includes embodiments in which more than one or all of the group members are present in, used in, or otherwise relevant to a given product or method.
[0142] In addition, the present disclosure encompasses all variants, combinations and arrangements in which at least one limitation, element, clause and illustrative term from at least one listed claim is introduced into another claim. For example, any claim subordinate to another claim may be modified to include at least one limitation seen in any other claim subordinate to the same basic claim. In the case where the element is presented in a list (such as in the form of a Markush group), each subgroup of the element is also disclosed, and any element may be removed from the group. It should be understood that, generally, in the case where the disclosure or the aspect of the disclosure is referred to as comprising specific elements and / or features, the embodiment of the disclosure or the aspect of the disclosure is composed of or substantially composed of such elements and / or features. For the purpose of brevity, these embodiments are not specifically stated in words herein. In the case of giving a range, endpoints are included. In addition, unless otherwise specified or otherwise clearly understood from the context and those of ordinary skill in the art, the value represented as a range in the different embodiments of the present disclosure may adopt any specific value or subrange within the described range, unless the context clearly indicates otherwise.
[0143] Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments disclosed herein. Such equivalents are intended to be encompassed by the following claims.
[0144] Examples
[0145] The following examples are intended to be illustrative and are not meant to limit the scope of the present disclosure in any way.
[0146] abbreviation
[0147] % Percent
[0148] g / t grams per ton
[0149] K2CO3 Potassium carbonate
[0150] Na2CO3 Sodium carbonate
[0151] Na2B4O7 Sodium Tetraborate
[0152] PA level professional analysis level
[0153] nd Undetermined
[0154] wt% weight percentage
[0155] NaOH Sodium hydroxide
[0156] Lithium
[0157] Nickel
[0158] Co Cobalt
[0159] Mn Manganese
[0160] Cu Copper
[0161] Al Aluminum
[0162] Fe Iron
[0163] Phosphorus
[0164] F Fluorine
[0165] Ca Calcium
[0166] Exemplary Elemental Analysis
[0167] Elemental analysis of the solid samples was performed by digestion in nitric acid and hydrochloric acid (feed sample and Examples 1 and 2) or by K2CO3-Na2CO3 / Na2B4O7 melt digestion and dissolution of the molten residue in hydrochloric acid (Examples 3 and 4).
[0168] The metals in the obtained sample solutions were determined by optical emission spectroscopy using inductively coupled plasma (ICP-OES).
[0169] Some element concentrations were also measured by X-ray fluorescence using an Epsilon 4DY-6024 from Malvern Panalytical using Malvern Panalytical Omnian software.
[0170] For sample preparation for the determination of the total fluorine content (waste samples), the elemental analysis of fluorine and fluoride was carried out according to DIN EN 14582:2016-12; the detection method was measurement with an ion-selective electrode. DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids, followed by acid-loaded distillation and determination of fluoride using an ion-selective electrode).
[0171] The total carbon of the gas obtained after combustion of the sample was determined by gas chromatography with a thermal conductivity detector.
[0172] Sulfur is determined by catalytic combustion of the sample in an inert gas / oxygen atmosphere, where it is converted into a mixture of SO2 and SO3. The SO3 formed is subsequently reduced to SO2 using copper particles. After drying and separation of the combustion gases, the sulfur is detected via thermal conductivity or IR spectroscopy and quantified as SO2.
[0173] Black matter
[0174] For the examples provided below, the black material was obtained by mechanically crushing lithium-ion batteries and then separating the black material as a fine powder from the other components of the lithium-ion batteries. The black material was obtained by a process involving pyrolysis of battery waste. The material contained small amounts of sulfur. The metals analyzed were present as oxidized compounds like MnO, CoO, NiO, as salts like LiF, LiAlO2, Li2CO3, and / or as zero oxidation state metals such as nickel, cobalt, and copper. Carbon was elemental carbon, primarily in the form of graphite with some soot or coke.
[0175] The composition of the black materials used in Examples 1 and 2 is provided in Table 1.
[0176] Table 1 : Composition of the black substance used in Examples 1 and 2.
[0177]
[0178]
[0179] Figure 3 The XRD pattern of the black substance is shown. Figure 3 , “a” indicates graphite, “b” indicates nickel-cobalt-manganese, “c” indicates NiO, “d” indicates CoO, “e” indicates MnO, “f” indicates Ni, and the remaining reflections correspond to lithium salts and impurities.
[0180] The composition of the black substance used in Example 3 is given in Table 2.
[0181] Table 2: The composition of the black substance used in Example 3:
[0182]
[0183] Cathode active material
[0184] The cathode active material (CAM) used in Examples 1 and 2 is a material known as HED TM NCM's commercially available CAM from BASF Corp. has a composition of 49.8 wt% Ni, 5.9 wt% Co, 2.6 wt% Mn, and 7.3 wt% Li.
[0185] Example 1
[0186] In this example, the black substance of Table 1 was brought into contact with an oxidizing acidic aqueous solution having a pH of less than 6, and then reduced with a reducing agent.
[0187] In a 0.75L jacketed reactor with baffles flushed with argon, 174.13g of black material was suspended in 337.21g of water. Then, 243.78g of H2SO4 (96wt%) was slowly added in 55min while stirring. The slurry was heated to 90°C during acid addition. After the acid addition was completed, the reactor contents were kept at 90°C for another 110min until the precipitation of hydrogen stopped. Air was then bubbled through the solution at 20 standard liters / hour (Nlph) for 2.5 hours while maintaining a slurry temperature of about 80°C. After an additional 30min, 25g of cathode active material was added. The reactor was kept under air for another 234min. Subsequently, SO2 was bubbled through the solution at 1.8Nlph for 51min. The composition of the leached residue is provided in Table 4.
[0188] Table 4 : Composition of the leaching residue from Example 1.
[0189] element concentration Al 3.2% Co 0.48% Cu 0.19% Fe 0.31% Li 0.14% Mn 0.23% Ni 0.73% F 0.4%
[0190] The recovery of each of the elements Ni, Co, Mn and Li was 98.2%, 98.1%, 99.2% and 99.0%, respectively. The recovery of Cu was 98.7% based on the analysis of the washed and dried leaching residue.
[0191] Example 2
[0192] In this example, a black substance having a composition shown in Table 1 was leached with sulfuric acid without introducing air as an oxidizing agent but in the presence of sulfur dioxide.
[0193] In a reaction vessel, 205g of black material and 25g of cathode active material were suspended in 563g of deionized water under an argon atmosphere. Under vigorous stirring with a Rushton turbine, 266g of sulfuric acid (96wt%) was slowly added to this mixture over a period of about 45min. At the same time, sulfur dioxide was fed into the reactor at a rate of 2.7g / h. The gas leaving the reactor was fed into a scrubber filled with 1779g of a solution of 50g of copper sulfate (II) pentahydrate in 1729g of water. After adding the acid, the reactor was heated to 96°C in 40min. The reactor was kept at this temperature for another 205min. Next, sulfur dioxide was stopped and the reactor was cooled to ambient temperature. The reactor contents were filtered, washed with water, and dried to obtain 61.65g of a black solid. 65min after the start of adding sulfuric acid and sulfur dioxide, the initially blue copper sulfate solution in the scrubber began to turn greenish and form a dark precipitate. The precipitate from the scrubber was also filtered, washed with water, and dried to give 0.116 g of a dark solid. The analysis of the solid residue is given in Table 7.
[0194] Table 7: Composition of the dried solid residue
[0195]
[0196]
[0197] The data in Table 7 show that an insoluble sulfur-containing phase is formed during the reaction, which is not present in the feed black material (Table 2). The molar ratio of Cu:S in the reactor product is 3:2. The molar ratio of Cu:S in the scrubber product is about 12:5. Without wishing to be bound by theory, it is believed that a mixture of copper sulfide (II) (CuS) and copper sulfide (I) (Cu2S) is formed in the reactor under reducing conditions in the presence of sulfur dioxide. The scrubber product is Cu2S with some adsorbed copper sulfate, which can explain the excess copper. The amount of copper in the filter residue of the reaction mixture corresponds to about 92% copper. In this filter residue, copper sulfide (I) is determined by XRD analysis through reflections of 2θ of 27.8°, 46.3° and 54.6°. Compared with pure copper sulfide (I), these reflections are slightly shifted to higher values, which indicates a substoichiometric composition.
[0198] Example 3
[0199] In this example, Example 2 was repeated with 186 g of the black material according to Table 2 and 21 g of the cathode active material.
[0200] The black substance and NCM are suspended in 588g of deionized water. This suspension is stirred at 700rpm, and 228g of sulfuric acid (96wt%) is slowly added in 52min. While the acid is added, sulfur dioxide gas is introduced into the reactor at a rate of 3g / h. During the acid addition, the reactor temperature rises to 52°C. After the acid addition ends, the reactor temperature is heated to 100°C, which is reached 90min after the acid addition ends. The addition of sulfur dioxide continues until the test ends 282min after the start of adding sulfuric acid / sulfur dioxide. The reactor is flushed with argon, and the suspension is diluted with 199.4g of deionized water. The cooled suspension is filtered, and the filter residue is washed with deionized water. The composition of the dried filter cake is given in Table 8.
[0201] Table 8: Composition of the dried solid residue (XRF analysis).
[0202]
[0203]
[0204] This residue was subjected to flotation to separate Cu sulfides, although the recoveries of Ni and Co were lower compared to Example 2. Flotation was performed as follows.
[0205] 80 g of the dried residue was dispersed in a 2L-Denver flotation cell with 800 g of deionized water by stirring at 1200 rpm for 15 min with the air inlet valve closed. 5000 g / t of solid Shellsol D40 (i.e. hydrogenated C11-C13 hydrocarbons) was then added as a graphite collector and dispersed again at 1200 rpm for 5 minutes. 200 g / t of solid methyl isobutyl carbinol (MIBC) was then added and stirred for another 5 min. After that, 270 g of water was added and the air inlet valve was opened, and flotation was started at an air flow rate of about 150 L / h. After 10 min, flotation was stopped by closing the air inlet valve again (first foam). Now 200 g / t of ethylhexyl potassium xanthate initial solid was added and stirred at 1200 rpm for 10 min. Another 200 g / t of MIBC initial solid was added, and then the air inlet valve was opened again. Next, another 10 min flotation (second foam) was performed. The data in Table 9 summarize the composition and yield of the two flotation stages.
[0206] Table 9: Composition of the dried solid flotation fraction (XRF analysis) (recovery).
[0207]
[0208] In Table 9, under the heading "Weight % of elements by total weight of fractions", the numbers without brackets are the grades of the elements in these fractions, and the numbers in brackets are the recoveries of these elements. For example, in the first froth obtained with Shellsol collector, the grade was 7.7% Cu and the recovery was (67%). For example, in the second froth fraction obtained with xanthate collector, the Cu grade was 22.5% and the recovery was only (6%). The final tailings are the residual material left after two consecutive flotation stages: a first stage with Shellsol as a carbon collector that also captures Cu and a second stage with xanthate specifically for capturing sulfide minerals that sulfide Cu. In Table 9, the yield (mass pull) is the total mass of solids recovered in the fractions divided by the mass of the solid feed. This exemplary flotation experiment demonstrates that copper can be enriched.
[0209] Comparing Example 1 with Examples 2 and 3, it is believed that the simultaneous reduction with SO2 in the contacting step, rather than a combined oxidation / reduction step such as a subsequent reduction with SO2 after the oxidation step (such as adding air as an oxidant) and / or the simultaneous addition of air and SO2, can result in the formation of copper (II) sulfide (CuS) and / or copper (I) sulfide (Cu2S). Such copper sulfide compositions can be separated from aqueous solutions by solid-liquid separation, such as filtration, sedimentation and / or centrifugation. Such copper sulfide compositions can be purified by solid-solid separation, such as flotation, magnetic separation using magnetic carrier particles capable of forming magnetic agglomerates with copper sulfide particles, gravity separation and / or gravity media separation.
Claims
1. A method for obtaining a composition comprising copper sulfide from a material, wherein the method comprises: contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide to form copper sulfide; wherein no oxidizing agent is added during the contacting step; wherein the material comprises one or more copper compounds selected from copper in a zero oxidation state, copper oxide and copper hydroxide; and The material comprises a certain amount of zero oxidation state metals having a standard redox potential less than 0 volts relative to a standard hydrogen electrode.
2. The method of claim 1, further comprising separating the composition comprising copper sulfide from the aqueous solution by solid-liquid separation.
3. The method of claim 1 or 2, further comprising purifying the composition comprising copper sulfide by solid-solid separation.
4. The method according to claim 2, wherein: The composition includes 0.1 weight percent to 100 weight percent of copper sulfide based on the total weight of the composition.
5. The method according to any one of claims 1 to 4, wherein: The acidic aqueous solution contains H2SO4.
6. The method according to any one of claims 1 to 5, wherein: The material is a lithium ion battery material, and the lithium ion battery material includes one or more selected from the following: a black substance, a cathode active material, a cathode, a cathode current collector foil, a cathode active material precursor, graphite, an anode, an anode current collector foil, and a combination thereof.
7. The method according to any one of claims 1 to 6, wherein: This material contains: 0 to 10 weight percent of lithium, 0.1 to 60 weight percent of nickel, 0 to 20 weight percent of cobalt, 0.1 to 20 weight percent of aluminum, 0 to 20 weight percent of iron, 0 to 20 weight percent of manganese, and 0 to 20 weight percent zinc; wherein each weight percentage is based on the total weight of the material; wherein an amount of at least one of the nickel, cobalt, aluminum, iron, manganese and zinc is present as a zero oxidation state metal; and Wherein the material has a molar ratio of copper to the amount of zero oxidation state metal in a range of 1:0.1 to 1:10, and the zero oxidation state metals have a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
8. The method according to any one of claims 1 to 7, wherein: The material or a precursor thereof is pyrolyzed prior to the contacting step.
9. The method according to any one of claims 1 to 8, wherein: Contacting the material with an acidic aqueous solution having a pH of less than 6 in the presence of sulfur dioxide causes the formation of hydrogen and hydrogen sulfide gases, and wherein, after the hydrogen and hydrogen sulfide gases are formed, the method includes adding an oxidant selected from the group consisting of O2, N2O, a mixture of air and 0.1 to 5 vol% sulfur dioxide, a mixture of oxygen and 0.1 to 5 vol% sulfur dioxide, and combinations thereof.
10. The method of any one of claims 1 to 9, further comprising adding air after the contacting step.
11. The method according to any one of claims 1 to 10, wherein: The acidic aqueous solution has an acid concentration ranging from 18 mol / L to 0.0001 mol / L.
12. The method according to any one of claims 1 to 11, wherein: During the contacting step, sulphur dioxide is fed as a gas at a rate ranging from 1 to 500 Nl / kg of the material.
13. The method according to any one of claims 1 to 12, wherein: After the contacting step, the method further comprises adding an additional material comprising one or more selected from the group consisting of metal oxides, metal hydroxides, metal carbonates, metal bicarbonates, and combinations thereof.
14. A method for recycling at least one battery material selected from the group consisting of lithium ion batteries, lithium ion battery waste, lithium ion battery production waste, lithium ion battery cell production waste, lithium ion cathode active materials, and combinations thereof, wherein the method comprises: Optionally, heat treating the at least one battery material at a temperature ranging from 350° C. to 900° C., mechanically pulverizing the at least one battery material to obtain a pulverized material, Optionally, sorting the comminuted material to obtain a fine fraction and a coarse fraction, and The comminuted material, optionally the fine fraction, the coarse fraction, or both the fine fraction and the coarse fraction, is subjected to a method according to any one of claims 1 to 13.
15. The method of any one of claims 1 to 14, further comprising smelting the composition comprising copper sulphide.
16. The method of any one of claims 1 to 14, further comprising calcining the composition comprising copper sulfide.
17. A composition comprising copper sulfide prepared by the method of any one of claims 1 to 16.
18. The method according to claim 2, wherein: The solid-liquid separation is selected from filtration, sedimentation, centrifugation, and combinations thereof.
19. The method according to claim 3, wherein: The solid-solid separation is selected from flotation, magnetic separation, gravity separation, heavy media separation, and combinations thereof.
20. The method according to any one of claims 1 to 14, wherein: Prior to and / or during the contacting step, one or more metals in zero oxidation state selected from Ni, Co, Mn, Fe and combinations thereof are added to the material.
21. The method according to claim 9, wherein: The oxidant is not added until after hydrogen is formed.
22. The method according to claim 10, wherein: Air is not added until at least 1 minute, at least 10 minutes, at least 30 minutes, at least 1 hour, or at least 2 hours after the contacting step begins.
23. The method according to any one of claims 1 to 22, wherein: Prior to the contacting step, the acidic aqueous solution is not bubbled with an oxidizing agent (eg, air).
24. The method according to any one of claims 1 to 23, wherein: Prior to the contacting step, no oxidizing agent other than sulfuric acid is added to the acidic aqueous solution.
25. The method according to any one of claims 1 to 24, wherein: At the beginning of the contacting step, less than 50 mol % of an oxidant other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of the copper in the zero oxidation state and the zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
26. The method according to any one of claims 1 to 25, wherein: At the beginning of the contacting step, less than 25 mol % of an oxidizing agent other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of the copper in the zero oxidation state and the zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
27. The method according to any one of claims 1 to 26, wherein: At the beginning of the contacting step, less than 10 mol % of an oxidizing agent other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of the copper in the zero oxidation state and the zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
28. The method according to any one of claims 1 to 27, wherein: At the beginning of the contacting step, less than 1 mol % of an oxidizing agent other than sulfuric acid is present in the acidic aqueous solution, based on the total moles of the copper in the zero oxidation state and the zero oxidation state metals having a standard redox potential of less than 0 volts relative to a standard hydrogen electrode.
29. The method according to claim 10, wherein: The subsequent air addition begins at least 1 minute after the contacting step begins, at least 10 minutes after the contacting step begins, at least 30 minutes after the contacting step begins, or at least 1 hour after the contacting step begins.
30. The method of claim 10, wherein: Subsequent air addition begins between 0 minutes and 2 hours after the start of this contacting step.
31. The method according to any one of claims 1 to 30, wherein: The composition comprising copper sulfide is separated by flotation in the presence of a xanthate, a dithiophosphate, a thiocarbamate, a xanthate formates, an ester of xanthate, and / or a mercaptobenzothiazole collector.
32. A method comprising leaching a material according to the method of any one of claims 1 to 31 to obtain an aqueous solution comprising metal ions, and separating the metal ions to obtain at least one substantially pure metal ion solution and / or at least one substantially pure solid metal ion salt.
33. The method according to any one of claims 1 to 32, wherein: Contacting the material with the acidic aqueous solution having a pH of less than 6 causes the formation of hydrogen gas, and contacting the acidic aqueous solution having a pH of less than 6 with the sulfur dioxide during the formation of hydrogen gas.